Plate-nanolattices at the theoretical limit of stiffness and strength - Cameron Crook (Nature Portfolio, 2020)
Plate-lattices are predicted to reach the upper bounds of strength and stiffness compared to traditional beam-lattices, but they are difficult to manufacture. Here, the authors use two-photon polymerization 3D-printing and pyrolysis to make carbon plate-nanolattices which reach those theoretical bounds, making them up to 639% stronger than beam-nanolattices.